The Shift of the Thematic Structure in English-Indonesian Translation of 'Flipped' Subtitles - Aini, Veny Nur; Wuli Fitriati, Sri; Anggani Linggar Bharati, Dwi (Universitas Negeri Semarang, 2020)
This study analysed the thematic structure in English-Indonesian translation of the movie subtitles entitled Flipped in order to explain the shift and modulation occurrences from the source text (ST) to the target text (TT). This research was initiated by the issue that Systemic Functional Linguistic (SFL) theory was possible to apply in translation research. This study was a descriptive qualitative research. The subjects of the study were the dialogues (English script and Indonesian subtitles) and the objects were the Thematic Structure Elements (Textual, Interpersonal, and Experiential Themes) of the movie. The findings showed that there were 259 shifts occurred within Textual Theme’s components, Interpersonal Theme’s components, Topical Theme’s components, Theme’s components, and between Theme-Rheme. Those indicated some shift and modulation types. There were 232 shifts found for 5 shift types and 40 shifts found for 6 modulation types. Moreover, there were two shift categories found (double changes). There were 23 shifts for 7 double changes categories. From this new categories, I inferred that it was possible if two types of shift or one type of shift + one type of modulation were together transform a sentence. On the other hand, it was impossible for two types of modulation were found in a sentence. In conclusion, Theme as the beginning of a sentence can be used as the first detector of the shift occurrence from ST to TT. We can see either the structure shift or the perspective shift from it. Therefore, translators and language learners can be helped by seeing this movement.